Obstructive Uropathy, Uncontrolled Diabetes and Emphysematous Pyelonephritis: A High-Risk Combination Requiring Intervention - Subash Kaushik TG; Aher, Nakul; Palaniyandi, Velmurugan; Sekar, Hariharasudhan; Krishnamoorthy, Sriram (Newer Frontiers in Urology, Edition 1, 2025)
Gas-forming organisms induce an acute kidney infection that results in parenchymal damage, which is known as emphysematous pyelonephritis. Renal function will be severely affected if it is not identified or treated. Even while the majority of patients have a very bad prognosis, things grow even worse if there is an active infection or urinary tract obstruction. The prognosis is further altered by fungal septicemia and uncontrolled blood sugar levels. In this case study, the case of a middle-aged man who arrived in the ER with extremely elevated blood sugar, altered sensorium, high temperature, chills, and rigidity, was described. Upon evaluation using an abdominal computed tomography, a 2 cm calculus was found at the uretero-pelvic junction blocking the drainage from the right kidney with class 3b emphysematous pyelonephritis extending to perinephric space and psoas sheath. Numerous studies have reported different prognostic markers and risk stratification methodologies that decide the patient's outcome. As a patient in the intermediate risk group, the patient required immediate glycemic management, correction of the acid-base imbalance, urgent stone disimpaction, and pelvicalyceal system decompression with percutaneous draining of the psoas and perinephric collections. This case study demonstrates how patients with gas-forming kidney infections can die from both blockage and uncontrolled blood sugar levels. To preserve the kidney and save the patient's life, there is a need to be vigilant, and well aware of this deadly combination, and make sure that a timely diagnosis is made, and the patient is prioritized appropriately.